Kemampuan Guru dalam Menyusun Kurikulum Tingkat Satuan Pendidikan - Herry Widyastono (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2012)
The objective of the study is to obtain the information on the teachers’ ability in enacting the school-based curriculum. This is a descriptive research using qualitative approach. The data collection was conducted in September 2011. The respondents of the research are from Jakarta, Bekasi, Depok, Bogor, and Tangerang as much of 150 teachers, and they are chosen based on the purposive technique sampling. They consist of 30 primary teachers, 50 junior high teachers, and 70 senior high teachers. Some of whom are teaching Math, Science,Physics, Chemistry, or Biology. The data of the document is analised, and the triangulation was conducted through focus discussion in a classroom (6 classroom), which then be continued by interviewing comprehensively to some of them in order to get the valid data. The researchconcludes that the teachers’ ability in writing up school-based curriculum (syllabus) which comprises the components of 1) standard competence; 2) basic competence; 3) core content; 4) learning activities; 5) indicator; 6) evaluation; 7) time allotment; and 8) learning resource are still very low and even most of them merely adobt other school curriculum or using them produced by book-publishers which are not actually suitable to themselves. It is therefore,advisable that the government should do some serious effort to redesign the in effect curriculum to become the national, province, district, and school curriculums.ABSTRAK Studi bertujuan untuk memperoleh informasi tentang kemampuan guru dalam menyusun kurikulum tingkat satuan pendidikan. Studi ini merupakan penelitian deskriptif yang menggunakan pendekatan kualitatif. Pengumpulan data dilaksanakan pada bulan September 2011. Responden berasal dari Jakarta, Bekasi, Depok, Bogor, dan Tangerang sebanyak 150 orang guru yang dipilih dengan teknik purposive sampling. Terdiri atas 30 orang guru SD, 50 orang guru SMP, dan 70 orang guru SMA, mengajar Matematika, Ilmu Pengetahuan Alam, Fisika, Kimia, atau Biologi. Teknik pengolahan datanya adalah studi analisis dokumen. Triangulasi dilakukan dengan cara diskusi fokus di dalam kelas (6 kelas), yang kemudian dilanjutkan dengan wawancara mendalam terhadap orang-orang tertentu untuk memvalidasi data dan informasi. Hasil studi menyimpulkan bahwa kemampuan guru dalam menyusun kurikulum tingkat satuan pendidikan (silabus), yang meliputi komponen: 1) standar kompetensi; 2) kompetensi dasar; 3) materi pokok; 4) kegiatan pembelajaran; 5) indikator; 6) penilaian; 7) alokasi waktu; dan 8) sumber belajar, masih sangat rendah, bahkan kebanyakan hanya mengadopsi kurikulum dari satuan pendidikan lain atau dari penerbit buku yang belum tentu sesuai dengan satuan pendidikannya. Oleh karena itu, disarankan kepada pemerintah pusat agar melakukan penataan ulang kurikulum tingkat satuan pendidikan menjadi kurikulum tingkat nasional, provinsi, kabupaten/kota, dan satuan pendidikan.